FREQUENCY OF LOW-BIRTH-WEIGHT INFANTS IN HEPATITIS C POSITIVE MOTHERS (The Research of Medical Science Review, 2025)
Objective: To determine frequency of low-birth-weight infants in hepatitis C positive mothers.Study Design: Cross Sectional Study. Settings: Department of Obstetrics and Gynecology, Duration of Study: Six months after the approval of synopsis(letter no. MNCH/admin/23/973 dated 27-10-23) Jan to June 2024. Methodology: A total of 172 participants. The inclusion criteria comprised pregnant women aged 18 to 45 years, with any parity, gestational age beyond 24 weeks, and confirmed hepatitis C infection, as determined by the presence of Anti-HCV antibodies in serum using a third-generation ELISA test. A thorough systemic and gynecological examination was conducted for each participant. A 5 ml blood sample was drawn from a peripheral vein and tested for Anti-HCV antibodies using a third-generation ELISA test in the hospital laboratory. Women diagnosed with hepatitis C were followed until delivery. The birth weight of each newborn was measured immediately after delivery using a standard infant weight machine, and the weight was recorded in grams. LBW was defined according to WHO criteria, as a birth weight of less than 2500 grams. RESULTS: The mean neonatal birth weight was 2887.46 grams (±488.30). The overall frequency of LBW in Hepatitis C-positive mothers was 36 out of 172 cases (20.9%), while 136 (79.1%) had normal birth weight infants. CONCLUSION: Our findings highlight a high burden of LBW, additional studies are necessary to clarify the precise pathophysiological mechanisms and optimal management strategies for this vulnerable population.